Psychological dualities in R.L.Stevenson's The Strange Case of Dr Jekyll and Mr Hyde - Valterová, Jana (Univerzita Pardubice, 2014)
The aim of this bachelor thesis is to analyse the psychological dualities of the Victorian society. The theoretical knowledge are confronted with the motive of a split personality in the novel The Strange Case of Dr Jekyll and Mr Hyde written by Robert Louis Stevenson. At first, there is a characteristic of the Victorian society with the emphasis on its dualities, such as the strict code of moral values. Further, there are introduced the main psychological concepts which developed in the 19th century and which profoundly influenced the perception of a human personality. The application of these theories in literature is shown on the analysis of the characters from Stevenson's novel.
Psychologické duality v díle R.L.Stevensona Podivuhodný případ doktora Jekylla a pana Hyda
Keywords: Podivuhodný případ doktora Jekylla a pana Hyda; Stevenson, Robert Louis; viktoriánské hodnoty; viktoriánská psychologie; Freud, Sigmund; Spencer, Herbert; Bain, Alexander; Strange Case of Dr Jekyll and Mr Hyde; Victorian values; Victorian psychology